2012
DOI: 10.1111/j.1399-6576.2012.02702.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane‐induced post‐conditioning in senescent hearts is attenuated by failure to activate reperfusion injury salvage kinase pathway

Abstract: We demonstrated that isoflurane post-conditions the heart in young but not in senescent rats. Failure to activate RISK pathway may contribute to attenuation of isoflurane-induced post-conditioning effect in senescent rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)], and especially the more recently identified survivor activating factor enhancement (SAFE) pathway [i.e. Janus kinase (JAK)/STAT3] play critical roles in the cardioprotection afforded by IsoPostC [30,31]. It is of interest that Goodman et al [32] reported, during ischaemic postconditioning, that JAK/STAT3 worked upstream of PI3K/Akt, and JAK/STAT3 activation alone was insufficient to provide cardioprotection in ischaemic postconditioning without subsequent PI3K/Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)], and especially the more recently identified survivor activating factor enhancement (SAFE) pathway [i.e. Janus kinase (JAK)/STAT3] play critical roles in the cardioprotection afforded by IsoPostC [30,31]. It is of interest that Goodman et al [32] reported, during ischaemic postconditioning, that JAK/STAT3 worked upstream of PI3K/Akt, and JAK/STAT3 activation alone was insufficient to provide cardioprotection in ischaemic postconditioning without subsequent PI3K/Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…9 This condition has been shown to induce beneficial effects in cardiac postconditioning studies with volatile anesthetics. 2,28,29 In the in vivo experiments, it is surprising that LVEDV was not preserved by argon despite its protective effect on LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…age-dependent impairment in ischaemia-induced neovascularisation might be due, at least in part, to oxidative stressrelated dysfunction of endothelial progenitor cells (Lam, 2015). elsewhere (Boengler, Schulz, & Heusch, 2009;Calabrese, 2016;Ferdinandy et al, 2014).…”
Section: Thismentioning
confidence: 99%
“…Pharmacological postconditioning with the anaesthetic agents sevoflurane or isoflurane reduced IS in the myocardium of young (3–5 months age) but not aged (20–24 months age) rats, and this was attributed to the failure to activate the pro‐survival RISK signalling pathway, comprising Akt and ERK1/2, and lack of inhibition of the mPTP opening (Chang et al, 2012; Li et al, 2013). Furthermore, pharmacological inhibition of glycogen synthase kinase 3β (GSK3β), using SB‐216763, reduced IS and inhibited mPTP opening in young (3–5 months age) but not aged (20–24 months age) rats (Zhu, Rebecchi, Glass, Brink, & Liu, 2011).…”
Section: Effect Of Age On Cardioprotection Treatmentsmentioning
confidence: 99%